(untitled) (American Journal of Islam and Society, 2018)
The International Institute of Islamic Thought (IIIT) organized a panel, entitled “Citizenship and Minorities in Contemporary Islam” at the 2017 American Academy of Religion (AAR) Annual Meeting. The panel was held at the John B. Hynes Veterans Memorial Convention Center in Boston, Massachusetts on Sunday, November 19, 2017. The panel was presided by Dr. Ermin Sinanović, IIIT’s Director of Research and Academic Programs, and included the panelists Dr. Ovamir Anjum, the Imam Khattab Endowed Chair of Islamic Studies at the Department of Philosophy and Religious Studies at University of Toledo; Dr. Mohammad Fadel, Associate Professor and Toronto Research Chair for the Law and Economics of Islamic Law at the University of Toronto Faculty of Law; and Dr. Basma Abdelgafar, Vice President of Maqasid Institute and Associate Professor of Public Policy ...